2014
DOI: 10.1038/jcbfm.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Early Small Vessel Disease Affects Frontoparietal and Cerebellar Hubs in Close Correlation with Clinical Symptoms—A Resting-State fMRI Study

Abstract: Cerebral small vessel disease, mainly characterized by white matter lesions and lacunes, has a high clinical impact as it leads to vascular dementia. Recent studies have shown that this disease impairs frontoparietal networks. Here, we apply resting-state magnetic resonance imaging and data-driven whole-brain imaging analysis methods (eigenvector centrality) to investigate changes of the functional connectome in early small vessel disease. We show reduced connectivity in frontoparietal networks, whereas connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 15 publications
8
52
1
Order By: Relevance
“…The functional metrics in the present study have been widely implemented to detect linear correlations with age (Biswal et al, 2009;Lopez-Larson et al, 2011;Premi et al, 2014;Zuo et al, 2012), behavioral measurements (Kwak et al, 2012;Ren et al, 2015;Schaefer et al, 2014;Tian et al, 2012;Wu et al, 2015;W. Xia et al, 2013), and clinical parameters Cai et al, 2015;Holiga et al, 2015;W.-C. Lin et al, 2015;Qiu et al, 2011;W.…”
Section: The Robust Linear Correlation Analysis Against Agementioning
confidence: 99%
“…The functional metrics in the present study have been widely implemented to detect linear correlations with age (Biswal et al, 2009;Lopez-Larson et al, 2011;Premi et al, 2014;Zuo et al, 2012), behavioral measurements (Kwak et al, 2012;Ren et al, 2015;Schaefer et al, 2014;Tian et al, 2012;Wu et al, 2015;W. Xia et al, 2013), and clinical parameters Cai et al, 2015;Holiga et al, 2015;W.-C. Lin et al, 2015;Qiu et al, 2011;W.…”
Section: The Robust Linear Correlation Analysis Against Agementioning
confidence: 99%
“…Functional connectivity is highly susceptible to motion-related artifacts, and because patients tend to move more than controls, there is a need for either real-time motion correction or improved post hoc removal of motion artifacts. 40 In addition, given that white matter lesions affect brain connectivity 41,42 and are reported to relate to behavioral deficits after stroke, 43 the variance explained by this factor needs to be accounted for when conducting functional connectivity analyses.…”
Section: Conclusion Considerations and Future Perspectivesmentioning
confidence: 99%
“…A few recent studies, however, showed that higher volumes of WMH are associated with reduced functional connectivity and activation of frontal regions 76 77…”
Section: Vascular Dementiamentioning
confidence: 99%